Parallel point reprojection - Reinhard, E.; Shirley, P.; Hansen, C. (IEEE Parallel and Large Data Visualization and Graphics Symposium 2001, 2001)
Improvements in hardware have recently made interactive ray tracing practical for some applications. However, when the scene complexity or rendering algorithm cost is high, the frame rate is too low in practice. Researchers have attempted to solve this problem by caching results from ray tracing and using these results in multiple frames via re-projection. However, the re-projection can become too slow when the number of samples that are reused is high, so previous systems have been limited to small images or a sparse set of computed pixels. To overcome this problem we introduce techniques to perform this re-projection in a scalable fashion on multiple processors.